2020
DOI: 10.1186/s13019-020-01142-x
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise external wrapping procedure for Stanford type A aortic dissection in extremely high-risk patients: case reports

Abstract: Background: Acute aortic dissection (AAD) is a rare, but a life-threatening condition which can lead to coronary, brachiocephalic or branch vessel malperfusion, as well as aortic valve insufficiency, or aortic rupture. Mortality of surgical treatment in high-risk or elderly patients with Type A Acute aortic dissection (TAAAD) still remains high, and treatment for such patients remains controversial. Case presentation: A new surgical approach which entails "stepwise external wrapping (SEW)" using a zeroporosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Suematsu et al reported the utilization of this technique in 82 patients since January 2015 and describe the new surgical approach which entails "stepwise external wrapping" using a zero-porosity artificial graft and applied in extremely high-risk patients. Patient outcomes after external wrapping were excellent with zero in-hospital mortality, successful aorta remodeling, and no aorta-related death during three years of follow up, thus very encouraging results of a feasible alternative to conventional graft replacement surgery [13,14].…”
mentioning
confidence: 77%
“…Suematsu et al reported the utilization of this technique in 82 patients since January 2015 and describe the new surgical approach which entails "stepwise external wrapping" using a zero-porosity artificial graft and applied in extremely high-risk patients. Patient outcomes after external wrapping were excellent with zero in-hospital mortality, successful aorta remodeling, and no aorta-related death during three years of follow up, thus very encouraging results of a feasible alternative to conventional graft replacement surgery [13,14].…”
mentioning
confidence: 77%
“…Intraoperative transesophageal echocardiography demonstrated mild aortic regurgitation. We then proceeded to treat the patient using the new surgical approach devised by us for high-risk patients, reported previously (stepwise external wrapping: SEW) [1,2]. The ascending aorta was carefully separated from the pulmonary arterial trunk and right pulmonary artery.…”
Section: Case Presentationmentioning
confidence: 99%
“…Patient outcomes after external wrapping were excellent with zero inhospital mortality, successful aorta remodeling, and no aorta-related death during 3 years of follow-up; thus, results of a feasible alternative to conventional graft replacement surgery were very encouraging. 13,14 While medical management is emerging as a reasonable approach in selected patients who are not surgical candidates, endovascular intervention for the treatment of type A AAD is rapidly progressing. Utilization of transcatheter therapies in the ascending aorta for treating type A AAD has demonstrated technical success in small studies, low early mortality rates, and relatively acceptable aorta-related mortality rates in the long term.…”
Section: Suematsu Et Al Reported the Utilization Of This Technique Imentioning
confidence: 99%
“…Suematsu et al reported the utilization of this technique in 82 patients since January 2015 and described the new surgical approach that entails “stepwise external wrapping” using a zero‐porosity artificial graft and is applied in extremely high‐risk patients. Patient outcomes after external wrapping were excellent with zero in‐hospital mortality, successful aorta remodeling, and no aorta‐related death during 3 years of follow‐up; thus, results of a feasible alternative to conventional graft replacement surgery were very encouraging 13,14 …”
mentioning
confidence: 92%